Inflation Targeting and Economic Growth in South Africa – An Econometric Analysis: Array - Rena, Ravinder; Kotsokoane, Kelebogile (Acta Universitatis Danubius. Œconomica, 2021)
The article aims to analyse the influence of inflation on economic growth in South Africa using quarterly data spanning from 2000-2018. The study is focusing on a quantitative research, exploratory research design and a positivism research philosophy with the variables of consumer price index, inflation, gross domestic product, interest rate and unemployment. The data set comprised of quarterly data from 2000 to 2018, extracted from the Statistics South Africa (Stats SA) website and also from the South African Reserve Bank (SARB). The Augmented Dickey-Fuller Furthermore, Phillips-Perron (PP) test and Kwiatkowski, Phillips, Schmidt and Shin (KPSS) results showed stationarity results at first difference. The serial correlation, diagnostic tests, normality test and heteroscedasticity passed expectations of the assumptions. The optimal lag selection was carried out by means of the Akaike Information Criterion (AIC) and the optimal lag length of two was selected. The existence of long-run equilibrium amongst the variables was tested using the Johansen co-integrated test. The Johansen co-integrated test indicated three co-integration equations, whereby the variables were found to be co-integrated at first difference. The VECM results showed that GDP is explained by lagged values of GDP, inflation and the consumer price index control variable in the short run. The relationship between economic growth and inflation targeting was found to exist. Moreover, the analyses reflected that there is a long-run relationship between inflation targeting and economic growth in South Africa. Additionally, monetary policy should be formulated with measures which are innovative and new to stabilise the exchange rate at a level that can be sustained. Furthermore, the government of South Africa is encouraged to continually align their economic policies and establish tight control on fiscal policy.